Tetralogy of Fallot: Current surgical perspective - Karl Tom (Wolters Kluwer Medknow Publications, 2008)
Tetralogy of Fallot (TOF) is an important lesion for all pediatric and congenital heart surgeons. In designing the most appropriate operation for children with TOF, the postoperative physiology should be taken into account, both in the short and long term. The balance between pulmonary stenosis (PS) and pulmonary insufficiency (PI) may be critical for preservation of ventricular function. A unified repair strategy that limits both residual PS and PI is presented, along with supporting experimental evidence, a strategy for dealing with coronary anomalies, and comments regarding best timing of operation.